FUTURE TRENDS IN MILK FAT CONTENT: A FIVE-YEAR FORECAST FOR ROMANIA AND THE EUROPEAN UNION - Raluca-Aniela GHEORGHE-IRIMIA; Dana TĂPĂLOAGĂ; Cosmin ȘONEA; Paul-Rodian TĂPĂLOAGĂ; Silviu-Ionuț BEIA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The present study investigates the trends and projections of milk fat content in Romania and the European Union (EU) from 2014 to 2029. The objective of this study was to employ time series analysis and regression modelling techniques in order to examine the evolution of milk fat content and evaluate the precision of predicted models. The findings from the research conducted in Romania indicate a consistent albeit moderate increase in milk fat content. The regression model adequately explains 90.81% of the observed variability. The predictive model exhibited a notable level of precision, as indicated by the low Mean Absolute Error (MAE) and Root Mean Squared Error (RMSE) values, which suggest a small disparity between the anticipated and observed values.Similarly, throughout the European Union, the milk fat content shown a more prominent and consistent increase, as indicated by the regression model which accounted for 99.16% of the variation. The reliability of the forecasting model is reinforced by positive statistical indicators, such as a narrow Mean Absolute Scaled Error (MASE) and Root Mean Squared Error (RMSE), indicating a strong predictive precision. The results indicate a persistent rise in milk fat levels in both Romania and the European Union, which may be linked to breakthroughs in dairy farming techniques, enhancements in feed quality, and genetic developments. It is anticipated that these patterns will persist, since the milk fat content in both locations is projected to remain within a steady and somewhat rising range during the extended prediction period. The findings of this study have significant implications for stakeholders within the dairy sector, presenting a dependable foundation for future strategic planning and decision-making pertaining to milk production and qualitative improvement.